Analisis SWOT UMKM Rocket Chicken Terhadap Keputusan Pembelian Konsumen - Ramadhanti, Reifa Galih; Yunita, Tyna (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
SWOT analysis is a systematic process for identifying various factors to develop a company's strategy. Rocket Chicken is a franchise that offers reasonably priced food and drink items derived from chicken at a lower cost than other businesses. The purpose of this study is to evaluate the influence of Rocket Chicken MSME goods' advantages, disadvantages, opportunities, and threats on customer purchase decisions. Data for this study comes from previous research used as references and employs descriptive qualitative methodologies. According to the study's findings, Rocket Chicken has a great chance of expanding and succeeding in the fast food industry if it adopts a smart approach that takes advantage of its advantages over disadvantages.